Ultrasonically generated pulsed water jet peening of austenitic stainless-steel surfaces. (April 2018) - Srivastava, Madhulika; Hloch, Sergej; Tripathi, Rupam; Kozak, Drazan; Chattopadhyaya, Somnath; Dixit, Amit Rai; Foldyna, Josef; Hvizdos, Pavol; Fides, Martin; Adamcik, Pavel
Abstract: In this study, the effects of pulsating water jets were investigated as a surface treatment process using circular and flat nozzles by considering the integrity of a stainless steel (AISI 304) surface. The local energy distribution was controlled by changing the traverse speed and the pulsating water jet (PWJ) effects were assessed in terms of the residual stress and strengthening effect. The strengthening effect of the process was evaluated by measuring the micro-hardness of the treated surface and by studying the impact of the treatment on the surface based on micro-structural analyses using scanning electron microscope (SEM). The residual stress of the subjected area was evaluated using X-ray diffraction technique. Based on the results from the studied samples, it was found that the initial tensile residual stress was relieved and converted to a compressive residual stress. An increase in the hardness of the treated samples was also observed as compared to the untreated samples up to certain depth along the cross-section of the treated region. The micro-structural examination of the samples revealed the plastic deformation that occurred during the treatment process. Additionally, the acoustic emission (AE) generated during the impact was used as an online monitoring tool for observing the behaviour of the elicited signals under different parametric conditions, and as a control mechanism for obtaining better results. The experimental results show that the pulsating water jet constitutes a new potential technology for surface treatment processes.